PENERAPAN TEKNOLOGI PENGOLAHAN SAMPAH ORGANIK BERBASIS ZERO WASTE YANG BERNILAI EKONOMIS DI SUMATERA BARAT - Deni Novia; Robi Amizar; Fitrimawati Fitrimawati; Syafrizayanti Syafrizayanti (Jurnal Hilirisasi IPTEKS, 2022)
Plastic waste gets special attention to deal with it, but the largest waste in the final disposal site is organic waste, about 60% dominates the amount of existing waste. Organic waste if processed and used for daily life can actually provide additional income if taken seriously. The purpose of this activity is to provide knowledge and skills for female partner organization partners, especially from students who live in West Sumatra, about zero waste so that it can process organic waste into several products that are useful and have economic value on a household scale. The activity methods were directives, counseling/awareness/socialization, training, mentoring and business consulting. The stages of implementation were 1) planning the right activities according to the needs of partners, 2) mentoring webinars, 3) evaluation. Based on the activity that have been carried out, it could be concluded that 1) Partners need assistants to solve the waste problem in Partner households, 2) The zero waste mentoring webinar activity had been carried out online using the zoom application, which was attended by more than 108 the participants who came from students and the public were enthusiastically by three presenters as well as reliable practitioners in their respective fields with the topics of eco enzymes, indigenous microorganisms (IMO), waste - maggot - compost. 3) Participants were very impressed with the zero waste webinar and asked to be followed up on other webinars. 4) The eco enzyme, MOL and compost training activities would be held offline and a visit to Minagot.